Opposite Roles of Wnt7a and Sfrp1 in Modulating Proper Development of Neural Progenitors in the Mouse Cerebral Cortex - Miao, Nan; Bian, Shan; Lee, Trevor; Mubarak, Taufif; Huang, Shiying; Wen, Zhihong; Hussain, Ghulam; Sun, Tao (Frontiers in Molecular Neuroscience, 2018)
The Wingless (Wnt)-mediated signals are involved in many important aspects of development of the mammalian cerebral cortex. How Wnts interact with their modulators in cortical development is still unclear. Here we show that Wnt7a and secreted frizzled-related protein 1 (Sfrp1), a soluble modulator of Wnts, are co-expressed in mouse embryonic cortical neural progenitors (NPs). Knockout of Wnt7a in mice causes microcephaly due to reduced NP population and neurogenesis, and Sfrp1 has an opposing effect compared to Wnt7a. Similar to Dkk1, Sfrp1 decreases the Wnt1 and Wnt7a activity in vitro. Our results suggest that Wnt7a and Sfrp1 play opposite roles to ensure proper neural progenitor progeny in the developing cortex.